SPE Annual Technical Conference and Exhibition 2011
DOI: 10.2118/147352-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Transport Phenomena and Multicomponent Sorption for Shale Gas and Coalbed Methane in an Unstructured Grid Simulator

Abstract: Shale gas and coal bed methane (CBM) assets have become increasingly important over the last decade, and are expected to become major energy sources for the future generations. However, there are unanswered fundamental physics and transport questions for each of these resources. Various physics-based approaches have been proposed and implemented to understand and simulate the flow mechanisms. However, the connectivity of organic and mineral matter is not fully understood and thus the exact transport mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…In the Appalachian Basin, the well performance from darker zones within Devonian shale with higher organic content is better than that from organic-poor gray zones (Schmoker 1980). Lu et al (1995) showed that the relationship between gas-adsorption capacity and TOC is approximately linear when the TOC is high, whereas for a very low TOC, illite plays an important role in gas storage in Devonian shales. The adsorption process in shale-gas reservoirs is mainly physical adsorption, which means that the adsorption is fully reversible, allowing gas molecules to completely adsorb and desorb, and the interaction force between the solid surface and the adsorbed gas molecules is controlled by the weak van der Waals force.…”
Section: Introductionmentioning
confidence: 99%
“…In the Appalachian Basin, the well performance from darker zones within Devonian shale with higher organic content is better than that from organic-poor gray zones (Schmoker 1980). Lu et al (1995) showed that the relationship between gas-adsorption capacity and TOC is approximately linear when the TOC is high, whereas for a very low TOC, illite plays an important role in gas storage in Devonian shales. The adsorption process in shale-gas reservoirs is mainly physical adsorption, which means that the adsorption is fully reversible, allowing gas molecules to completely adsorb and desorb, and the interaction force between the solid surface and the adsorbed gas molecules is controlled by the weak van der Waals force.…”
Section: Introductionmentioning
confidence: 99%
“…Second, there are also natural fractures in shale, which can play an important role in formation of hydraulic fracture geometry and depletion of the reservoirs. Third, adsorbed gas contributes a significant fraction of total original gas in place (Leahy-Dios et al 2011), although the impact on EUR and production is not well understood. Fourth, the history of drilling horizontal wells in the Eagle Ford shale is relatively short, with first production from these wells in 2008.…”
mentioning
confidence: 99%
“…In shale gas reservoirs, the gas adsorbed on organic material surfaces is considered as the main source in the pores (Leathy-Dios et al, 2011). With the pressure decreasing during the gas production, the gas adsorbed on the matrix will release and contribute to the gas production.…”
Section: Gas Adsorption and Desorptionmentioning
confidence: 99%